The Transfer of Ownership Rights of Bengkok Land Through Land Swap Agreements - Haris Budiman; Bias Lintang Dialog; Mimin Mintarsih (UNIFIKASI : Jurnal Ilmu Hukum, 2020)
The process of transferring bengkok land ownership rights through land swap agreements is frequently done, but due to lack of understanding of the legislations, the transfer of land rights often experiences various problems. This study aims to find out the mechanism of transferring bengkok land ownership rights through land swap agreements based on the legislations as well as the process of certifying bengkok land into proprietary land. This descriptive-analytic study applied an empirical juridical approach. The results showed that the mechanism of transferring bengkok land ownership rights through land swap agreements in Kuningan District is regulated in Kuningan District Regulation No. 44 of 2017 concerning Management of Village Assets. Meanwhile, the process of certifying bengkok land into proprietary land is regulated in Article 17 of Government Regulation No. 27 of 2014 concerning Management of State/Regional Property. In conclusion, the process of transferring land ownership rights, especially state-owned land, shall to be done in a written form and is based on the applicable legislation. Peralihan Hak Milik Tanah Bengkok Melalui Perjanjian Tukar Guling Proses peralihan hak milik tanah bengkok melalui perjanjian tukar guling sering dilakukan namun karena ketidak pahaman terhadap peraturan perundang-undangan, peralihan hak milik atas tanah tersebut mengalami berbagai permasalahan. Tujuan penelitian adalah untuk mengetahui mekanisme peralihan tanah bengkok melalui perjanjian tukar guling menurut perundang-undangan dan proses pensertifikatan tanah bengkok menjadi tanah hak milik. Jenis penelitian deskriptif-analistis dengan pendekatan yuridis empiris. Hasil penelitian mengemukakan bahwa Mekanisme peralihan tanah bengkok melalui perjanjian tukar guling di Kabupaten Kuningan diatur dalam Peraturan Bupati Kuningan Nomor 44 Tahun 2017 tentang Pengelolaan Aset Desa dan Proses pensertifikatan tanah bengkok menjadi tanah hak milik diatur dalam Pasal 17 Peraturan Pemerintah Nomor 27 Tahun 2014 adalah pengalihan kepemilikan barang negara/daerah. Kesimpulannya Dalam proses perjanjian tukar menukar tanah terutama tanah milik negara perlunya dilakukan secara tertulis dan sesuai dengan peraturan perundangan yang berlaku.